INTERACTIVE LEARNING PLATFORM FOR PROGRAMMING WITH GAMIFICATION MECHANICS (Uzbekistan Open Conference, 2025)
The article describes the development and implementation of an interactive programming learning platform that integrates elements of gamification to increase student engagement and motivation. The platform aims to solve the problem of low absorption rates of programming skills through traditional teaching methods. The system architecture, key game elements (points, levels, achievements, ratings), and technologies used are described. It is emphasized that the combination of educational content and game mechanics contributes to the formation of a sustained interest in programming and active independent learning. Prospects for scaling the platform are presented.